A space-time mosaic of seawater carbonate chemistry conditions in the north-shore Moorea coral reef system - Dişa, Deniz; Münnich, Matthias; Vogt, Meike; Gruber, Nicolas (Frontiers in Marine Science, 2022)
The interplay between ocean circulation and coral metabolism creates highly variable biogeochemical conditions in space and time across tropical coral reefs. Yet, relatively little is known quantitatively about the spatiotemporal structure of these variations. To address this gap, we use the Coupled Ocean Atmosphere Wave and Sediment Transport (COAWST) model, to which we added the Biogeochemical Elemental Cycling (BEC) model computing the biogeochemical processes in the water column, and a coral polyp physiology module that interactively simulates coral photosynthesis, respiration and calcification. The coupled model, configured for the north-shore of Moorea Island, successfully simulates the observed (i) circulation across the wave regimes, (ii) magnitude of the metabolic rates, and (iii) large gradients in biogeochemical conditions across the reef. Owing to the interaction between coral net community production (NCP) and coral calcification, the model simulates distinct day versus night gradients, especially for pH and the saturation state of seawater with respect to aragonite (Ωα). The strength of the gradients depends non-linearly on the wave regime and the resulting residence time of water over the reef with the low wave regime creating conditions that are considered as “extremely marginal” for corals. With the average water parcel passing more than twice over the reef, recirculation contributes further to the accumulation of these metabolic signals. We find diverging temporal and spatial relationships between total alkalinity (TA) and dissolved inorganic carbon (DIC) (≈ 0.16 for the temporal vs. ≈ 1.8 for the spatial relationship), indicating the importance of scale of analysis for this metric. Distinct biogeochemical niches emerge from the simulated variability, i.e., regions where the mean and variance of the conditions are considerably different from each other. Such biogeochemical niches might cause large differences in the exposure of individual corals to the stresses associated with e.g., ocean acidification. At the same time, corals living in the different biogeochemical niches might have adapted to the differing conditions, making the reef, perhaps, more resilient to change. Thus, a better understanding of the mosaic of conditions in a coral reef might be useful to assess the health of a coral reef and to develop improved management strategies.